Prevalence and predictors of social anxiety disorders among Malaysian secondary school students during the COVID-19 pandemic: exploring the influence of internet gaming disorder and impulsivity - Nor Firdous Mohamed (Tanjung Malim, 2023)
Prevalence and predictors of social anxiety disorders among Malaysian secondary school students during the COVID-19 pandemic: exploring the influence of internet gaming disorder and impulsivity by Nor Firdous Mohamed